How do health content creators perform well? An integration research of short video and livestream behaviors - Liu, Jing; Ye, Qing; Wu, Hong; Ma, Rongyang; Guo, Shanshan; Long, Han (Frontiers in Public Health, 2024)
Introduction Short-video platforms have demonstrated vast potential for health education. To meet diverse user requirements, many short-video platforms have integrated livestreaming functionalities. This integration presents challenges for health content creators in formulating effective performance strategies, including decisions about which format to use (short video or livestream) and what type of content to produce. This study utilizes panel data from a prominent short-video platform in China to empirically investigate the impact of different forms and content characteristics on the performance of health content creators. Methods We conducted an empirical analysis using panel data obtained from a leading short-video platform in China. Our analysis focused on understanding how the behaviors associated with short videos and livestreaming impact the performance of health content creators. We examined form-level differences, analyzing the distinct roles of short video and livestreaming behaviors. Additionally, we explored content-level characteristics, investigating the effects of content coverage, health knowledge content, and advertising content on both short-term and long-term performance. The moderation effects of the creator’s occupation and certification type were also analyzed. Results Our form-level analysis revealed that health creators’ behaviors in short videos and livestreaming play distinct roles in their performance. Livestreaming behaviors resulted in short-term economic returns, while short video behaviors had a more significant effect on follow-ups, which are often viewed as long-term, more sustainable performance indicators. Content-level analysis showed that content coverage and health knowledge content enhance long-term performance but do not increase short-term performance. Conversely, advertising content was found to be essential for securing short-term financial income. The study also identified that the creator’s occupation and certification type moderate the impact of content on performance. Conclusion This study integrates two media forms (short video and livestream), providing direct insights into the performance of health content creators in the realm of health education. Health content creators need to strategically balance their use of short videos and livestreaming to optimize both short-term and long-term performance outcomes. Specifically, increasing content coverage and health knowledge can enhance long-term engagement, while incorporating advertising content is crucial for immediate financial gains.